A review of recent advances in water-gas shift catalysis for hydrogen production - Parisa Ebrahimi (14152392) (2022)
The water-gas shift reaction (WGSR) is an intermediate reaction in hydrocarbon reforming processes, considered one of the most important reactions for hydrogen production. Here, water and carbon monoxide molecules react to generate hydrogen and carbon dioxide. From the thermodynamics aspect, pressure does not have an impact, whereas low-temperature conditions are suitable for high hydrogen selectivity because of the exothermic nature of the WGSR reaction. The performance of this reaction can be greatly enhanced in the presence of suitable catalysts. The WGSR has been widely studied due do the industrial significance resulting in a good volume of open literature on reactor design and catalyst development. A number of review articles are also available on the fundamental aspects of the reaction, including thermodynamic analysis, reaction condition optimization, catalyst design, and deactivation studies. Over the past few decades, there has been an exceptional development of the catalyst characterization techniques such as near-ambient x-ray photoelectron spectroscopy (NA-XPS) and in situ transmission electron microscopy (in situ TEM), providing atomic level information in presence of gases at elevated temperatures. These tools have been crucial in providing nanoscale structural details and the dynamic changes during reaction conditions, which were not available before. The present review is an attempt to gather the recent progress, particularly in the past decade, on the catalysts for low-temperature WGSR and their structural properties, leading to new insights that can be used in the future for effective catalyst design. For the ease of reading, the article is divided into subsections based on metals (noble and transition metal), oxide supports, and carbon-based supports. It also aims at providing a brief overview of the reaction conditions by including a table of catalysts with synthesis methods, reaction conditions, and key observations for a quick reference. Based on our study of literature on noble metal catalysts, atomic Pt substituted Mn3O4 shows almost full CO conversion at 260 °C itself with zero methane formation. In the case of transition metals group, the inclusion of Cu in catalytic system seems to influence the CO conversion significantly, and in some cases, with CO conversion improvement by 65% at 280 °C. Moreover, mesoporous ceria as a catalyst support shows great potential with reports of full CO conversion at a low temperature of 175 °C. Other Information Published in: Emergent Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s42247-020-00116-y